2019
DOI: 10.1016/j.jcot.2018.08.019
|View full text |Cite|
|
Sign up to set email alerts
|

Innovative regenerative medicine in the management of knee OA: The role of Autologous Protein Solution

Abstract: Osteoarthritis (OA) is one of the most common causes of chronic disability in adults due to pain and altered joint function. Although most patients report pain and functional limitation, symptoms, age of onset and disease progression are extremely variable. While inflammation could play a central role in the OA pathogenesis and progression, many underpinning mechanisms are still unclear. A number of proinflammatory mediators have been found in OA joints and could play a role, such as IL-1, IL-6, IL-7, IL-8, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…To date, the outcomes of 1229 patients involved in studies evaluating the effect of injection of ACS/APS have been reported ( Table 2). The adverse reactions noted in these patients have been similar to the intraarticular administration of other therapeutic agents [17,40]. Additionally, they have been of a transient and self-limiting type [12,41].…”
Section: Safety Profile and Morbidity Of Intraarticular Injections Ofmentioning
confidence: 68%
See 4 more Smart Citations
“…To date, the outcomes of 1229 patients involved in studies evaluating the effect of injection of ACS/APS have been reported ( Table 2). The adverse reactions noted in these patients have been similar to the intraarticular administration of other therapeutic agents [17,40]. Additionally, they have been of a transient and self-limiting type [12,41].…”
Section: Safety Profile and Morbidity Of Intraarticular Injections Ofmentioning
confidence: 68%
“…In general, both ACS and APS are prepared from autologous peripheral blood, the volume of which can vary between 10 and 60 ml depending on the manufacturer kit [20,37,38]. The obtained blood sample is further conditioned by incubation with glass beads and centrifugation, leading to an increase in the production of IL-1Ra as well as multiple other cytokines and growth factors [17,20].…”
Section: Basic Science Of Acs/aps Production Methodsmentioning
confidence: 99%
See 3 more Smart Citations